On the Way to Life-domains Balance: Success Factors and Obstacles - Harald Lothaller (Intergenerational Justice Review)
During the ‘rush hour of life’, people face various challenges from different life domains simultaneously: they have to fulfill a number of different obligations at their workplace, at home, and elsewhere  of life (e.g., getting a job and starting a career, establishing a family, moving towards getting their own home, but also meeting people, part taking in leisure activities, etc.). The article examines the factors that have positive and negative effects on the transition from one life domain towards another. In addition, by focusing on the situation of dual-earner couples with young children it briefly illustrates why life-domains balance is significantly linked to the ‘rush hour of life’.